Comparison of the photoprotective effect between hydrolyzed and aglycones flavonoids as sunscreen: A systematic review (2020)
ABSTRACT: Currently, there is growing evidence of the role of polyphenols as protection agents against ultraviolet radiation (UVR), both in plant and animal cells, especially flavonoids, which are considered beneficial compounds that increase photoprotection of sunscreen formulations. The objective of this systematic review is to analyze if there is an increase in photoprotection of the hydrolyzed forms of polyphenols, specifically of flavonoids, such as quercetin and kaempferol, with respect to their corresponding glycosides, which are present in polar extracts of aerial parts of plants. Following the PRISMA guidelines, the systematic review was carried out in three electronic databases (Science Direct, Pubmed, and Embase) to identify the main articles that evaluated the effect of polyphenols against UVR protection. From a total of 1,230 research articles found, 21 met the inclusion parameters, of which 13 studies evaluated extracts isolated from different plants, and one study evaluated an agroindustrial residue. In all the cases, the main constituents were characterized as flavonoid compounds, including some of the compounds of interest of this revision. The effect of the pure compounds rutin and quercetin, as photoprotection enhancers, was evaluated in seven articles. Although a conclusive answer to the objective question of this systematic review could not be obtained, all the studies confirmed the biological activity of the polyphenols as photoprotector.